An Evaluation Study on Electric Appliance Characteristics and Load Patterns in Residential Buildings - Thongsuk, Surakit; Songsukthawan, Panapong; Ananwattanaporn, Santipont; Sottiyaphai, Chayanut; Ngaopitakkul, Atthapol; Jettanasen, Chaiyan; Pothisarn, Chaichan (My University, 2026)
Energy usage in residential buildings has been constantly increasing as work-from-home trends continue to maintain popularity. To improve energy efficiency, the load profile and electric appliances in households need to be established and analyzed. This study aims to evaluate the characteristics of electric appliances that are commonly used in residential buildings under various operating conditions. An experimental setup with household electric appliances was built, and power quality meters were installed to assess the patterns under various operating conditions. In addition, the usage patterns were used to construct the daily load profile and analyze the energy consumption in residential buildings. The results demonstrate that load patterns constructed from actual measurements can achieve an accurate depiction of energy usage in residential buildings. The obtained load profile can be used in load control to improve energy efficiency and the application of renewable energy in demand reduction.
Keywords: Building Energy Usage; Electric Application; Load Pattern